Novel Type of Specialized Transduction for CTXφ or Its Satellite Phage RS1 Mediated by Filamentous Phage VGJφ in Vibrio cholerae - Campos, Javier (American Society for Microbiology, 2003)
The main virulence factor of Vibrio cholerae, the cholera toxin, is encoded by the ctxAB operon, which is contained in the genome of the lysogenic filamentous phage CTXφ. This phage transmits ctxAB genes between V. cholerae bacterial populations that express toxin-coregulated pilus (TCP), the CTXφ receptor. In investigating new forms of ctxAB transmission, we found that V. cholerae filamentous phage VGJφ, which uses the mannose-sensitive hemagglutinin (MSHA) pilus as a receptor, transmits CTXφ or its satellite phage RS1 by an efficient and highly specific TCP-independent mechanism. This is a novel type of specialized transduction consisting in the site-specific cointegration of VGJφ and CTXφ (or RS1) replicative forms to produce a single hybrid molecule, which generates a single-stranded DNA hybrid genome that is packaged into hybrid viral particles designated HybPφ (for the VGJφ/CTXφ hybrid) and HybRSφ (for the VGJφ/RS1 hybrid). The hybrid phages replicate by using the VGJφ replicating functions and use the VGJφ capsid, retaining the ability to infect via MSHA. The hybrid phages infect most tested strains more efficiently than CTXφ, even under in vitro optimal conditions for TCP expression. Infection and lysogenization with HybPφ revert the V. cholerae live attenuated vaccine strain 1333 to virulence. Our results reinforce that TCP is not indispensable for the acquisition of CTXφ. Thus, we discuss an alternative to the current accepted evolutionary model for the emergence of new toxigenic strains of V. cholerae and the importance of our findings for the development of an environmentally safer live attenuated cholera vaccine.